Hepatitis B e Antigen–Negative Chronic Hepatitis B - Rashid, MH; Alim, MA; Khan, MMR; Rahman, MK; Chowdhury, MMH; Ekram, ARM Saifuddin; Ali, M Obaidullah Ibne; Khanam, K; Mohanta, DK (TAJ: Journal of Teachers Association, 2018)
Abstract not available TAJ 2012; 25: 90-96